Pendampingan Labelisasi Lanskap Linguistik Multilingual Destinasi Wisata Bangkalan di Era New Normal - Putri Nur Diana; Tazkiyatul Wildaniyah; Tiara Agil Tri Oktavia; Rosyida Ekawati (Jurnal Ilmiah Pangabdhi, 2022)
Linguistic landscapes have an important role in the public sphere as the use of language such as informative and educational. Various languages can be displayed in the linguistic landscape in tourist destinations such as Cakraningrat Museum in Bangkalan, Madura, which presents a linguistic landscape (LL) in Indonesian and English. However, some linguistic landscapes have not provided complete information about the relics. In addition, the increase in tourists, both local and foreign tourists, meanwhile the language presented in the linguistic landscape is still limited. Based on these problems, through this civil engagement program, LL labeling is carried out to add information about relics and improve the condition of the existing linguistic landscape as a renewal program in the new normal era. The implementation method of service consists of several stages, such as planning, preparation, LL execution and translation, labeling, and preservation. The output of this civic engagement activity is that all relics are equipped with multilingual LL (Indonesian, English, and Madurese).